EVALUATION OF ISLAMIC EDUCATION LEARNING PROGRAM BY USING COUNTENANCE EVALUATION MODEL - Suryadi, Ahmad; Rasyid, Muh. Nur Akbar; Syamsudduha, St. (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
This study aims to determine: (1) the quality of preparation, (2) the quality of implementation, and (three) the impact of students' learning on the implementation of PAI clump learning at MTs Arifah Gowa. This research is an assessment model used is Countenance Stake. The source of data in this study is the PAI clump subject teacher of MTs Arifah Gowa as many as 9 people. The research methods used are interviews, observation and documentation. The data analysis technique used means Miles and Huberman data analysis technique. The results showed that (1) the quality of learning planning for PAI subjects in the independent curriculum is categorized as good, (2) the application process and learning evaluation are categorized as good and (3) student learning outcomes in PAI subjects are categorized as good.